PRICE CONSCIOUSNESS DALAM PRIVATE LABEL ATTITUDES UNTUK MENINGKATKAN PRIVATE LABEL PURCHASE (Fokus Ekonomi, 2011)
Today high competition is happen in business retail, to face this condition Giant try hard to increase their products private label through the increasing of customer interest toward it. Price consciousness has major role in this condition. The aim of this study is to test the effect of price consciousness on private label attitude and the effect of private label attitude on private label purchase. There are 86 respondents in this research who have knowledge product private label Giant. Using regression analysis, the result show that price consciousness has no impact on private label attitude, while private label attitude affect on private label purchase.